Development of a Telegram Bot to Determine the Level of Technological Readiness - D. I. Suntsova; V. A. Pavlov; Z. V. Makarenko; P. P. Bakholdin; A. S. Politsinsky; A. S. Kremlev; A. A. Margun (Ekonomika Nauki)
The article proposes a Telegram bot to automate the process of assessing the readiness level of the technology. Flowcharts reflecting the algorithm of the bot, and images demonstrating the appearance of its interface are presented. To confirm the correct operation of the Telegram bot, a random project was taken, its main characteristics were highlighted, and based on them, a conclusion about the technology readiness level was made in two ways: by expert evaluation in accordance with the national standard and using a bot running on a personal computer with the Windows operating system and on a mobile device with the Android operating system. With equal input data, the conclusion about the readiness level of the technology obtained at the output of the algorithm coincides with the result of the expert assessment. It is proposed to use the Telegram bot as a source of an additional opinion about the level of technological readiness of the project.